Aktivitas Anti Inflamasi dan Penyembuhan Luka dari Ekstrak Kulit Batang Murbei (Morus alba L.) : Anti-inflammatory and Wound Healing Activities of Mulberry Barks (Morus alba L.) Extract - Lallo, Subehan; Hardianti, Besse; Umar, Halim; Trisurani, Widya; Wahyuni, Andi; Latifah, Mauizatul (Universitas Tadulako, 2020)
Mulberry (Morus alba L.) leaf has been used as a traditional medicine for treatment of some tropical diseases and also popular using for silkworm feed. On this research, anti-inflammatory and wound healing activities of the bark extract has been investigated in vivo. The bark was extracted with three organic solvent in a different polarity to carry out a group compounds in n-hexane extract (EH), Eto-Ac extract (EE), and EtOH extract (EO). Anti-inflammatory was investigated on inflammatory mice induced by 1% carrageenan. Among the extract (200mg/kg BW), EE showed strongly decrease inflammation by 42% than the other extract and stronger than the positive control, Na-diclofenac. Further investigation on healing effect of wound and burn injury which was tested at concentration of 1% topically to each extract. All the extract significantly showed healing activity, among them EE was observed as the stronger one while slightly less than the positive control. This result indicated that the most active compounds on anti-inflammatory and healing wounded was extracted with ethyl acetate that could be used for drug discovery.